Complaints about dental practitioners: an analysis of 6 years of complaints about dentists, dental prosthetists, oral health therapists, dental therapists and dental hygienists in Australia. (16th July 2018) - Thomas, LA; Tibble, H; Too, LS; Hopcraft, MS; Bismark, MM
Abstract: Background: Previous research has found dental practitioners at elevated risk of complaint compared with other health professions. This study aimed to describe the frequency, nature and risk factors for complaints involving dental practitioners. Methods: We assembled a national dataset of complaints about registered health practitioners in Australia between January 2011 and December 2016. We classified complaints into 23 issues across three domains: health, performance and conduct. We compared rates of complaints about dental practitioners and other health practitioners. We used negative binomial regression analysis to identify factors associated with complaints. Results: Dental practitioners made up 3.5% of health practitioners, yet accounted for approximately 10% of complaints. Dental practitioners had the highest rate of complaints among fourteen health professions (42.7 per 1000 practitioners per year) with higher rates among dentists and dental prosthetists than allied dental practitioners. Male practitioners were at a higher risk of complaints. Most complaints about dentists related to treatments and procedures (59%). Around 4% of dentists received more than one complaint, accounting for 49% of complaints about dentists. In 60% of closed cases no regulatory action was required. Around 13% of complaints resulted in restrictive actions, such as conditions on practice. Conclusion: Improved understanding of patterns may assist regulatory boards and professional associations to ensure competent practice and protect patient safety.